Automated geometrical evaluation of a plaza (town square). (June 2016) - Zawidzki, M.
Abstract: This paper presents a method for an automated geometrical evaluation (AGE) intended as a design support tool for urban design of a plaza ( P ). AGE is based on three normalized properties derived from a plan of P, namely: smallness, enclosure, and regularity. 19 worldwide plazas have been evaluated by 20 respondents in, what is called here, human subjective evaluation (HSE). A brief analysis of HSE including the identification of redundant categories is presented. Two P evaluation methods based on all four ( S, C, E, R ) and selected three ( S, E, R ) properties are discussed. Good agreement of AGE based on S, E, and R (NPSER ) with HSE is shown. P quality rating (excellent, good, fair) based on NPSER is introduced. Exceptional cases are briefly discussed.